2003
DOI: 10.1074/jbc.m308261200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding Determines Whether CD46 Is Internalized by Clathrin-coated Pits or Macropinocytosis

Abstract: CD46 is a ubiquitous human cell surface receptor for the complement components C3b and C4b and for various pathogens, including the measles virus and human herpes virus 6. Ligand binding to CD46 affects (i) protection of autologous cells from complement attack by breakdown of complement components, (ii) intracellular signals that affect the regulation of immune cell function, (iii) antigen presentation, and (iv) down-regulation of cell surface CD46. Recent evidence indicates that CD46 signaling can link innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 76 publications
5
67
0
Order By: Relevance
“…Multiple lines of evidence strongly suggest that H/F-LVs use entry into quiescent T cells via macropinocytosis: (i) IEPA inhibited H/F-LV T cell entry; (ii) H/F-LV entry was shown to be dependent on the actin cytoskeleton and microtubule formation, as it was inhibited by the inhibitors cytochalasin and nocodazole; (iii) blebbistatin, which prevents membrane blebbing, also decreased H/F-LV entry; (iv) the PI3K inhibitor LY294002 inhibited H/F-LV T cell entry completely; and (v) genistein affected H/F-LV entry, suggesting that tyrosine kinase activity plays a role in H/F-LV entry into quiescent T cells. These data are in accordance with the finding that contact of Edm H with CD46-expressing cells induces internalization of this receptor by macropinocytosis (9). It was hypothesized that MV LV infection of lymphocytes induced rearrangement of the actin network, and it was proposed that this allowed proviral transport into the nucleus in the absence of stimulation (6).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Multiple lines of evidence strongly suggest that H/F-LVs use entry into quiescent T cells via macropinocytosis: (i) IEPA inhibited H/F-LV T cell entry; (ii) H/F-LV entry was shown to be dependent on the actin cytoskeleton and microtubule formation, as it was inhibited by the inhibitors cytochalasin and nocodazole; (iii) blebbistatin, which prevents membrane blebbing, also decreased H/F-LV entry; (iv) the PI3K inhibitor LY294002 inhibited H/F-LV T cell entry completely; and (v) genistein affected H/F-LV entry, suggesting that tyrosine kinase activity plays a role in H/F-LV entry into quiescent T cells. These data are in accordance with the finding that contact of Edm H with CD46-expressing cells induces internalization of this receptor by macropinocytosis (9). It was hypothesized that MV LV infection of lymphocytes induced rearrangement of the actin network, and it was proposed that this allowed proviral transport into the nucleus in the absence of stimulation (6).…”
Section: Discussionsupporting
confidence: 79%
“…Several reports support the idea that macropinocytosis can act as an entry route for many pathogens, including viruses such as vaccinia virus (19,32), adenovirus (2,46), HIV (30,53), and the Nipah paramyxovirus (35). In addition, it was reported that addition of soluble Edm Hgp to cells induced internalization of the Edm H receptor complex by macropinocytosis (9). In all these cases, specific vector-receptor interactions are required to trigger macropinocytosis.…”
Section: Quiescent T Cell Entry Of H/f-lvs Might Occur Through Macropmentioning
confidence: 90%
“…Antibodies were mouse anti-human CD3, CD28, CD4, CD8, CD1a, CD14, CD11a, CD56, perforin (␦G9), and isotype-matched controls (BD Biosciences, San Diego, CA), Alexa Fluor secondary antibodies (Molecular Probes, Eugene, OR), and rabbit polyclonal to TfR and to CD46 (18). CD8 ϩ T cell and CD56 ϩ NK cell isolation kits were from Miltenyi Biotec (Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, ligation of CD46 can mediate direct effects on T cell function, such as inducing regulatory T cells (15) and preventing cytotoxic T lymphocyte (CTL) activation (14). CD46 interacts with a polarity network in epithelial cells and T cells (16,17), and ligation of CD46 by measles viruses induces polarization of epithelial cells (18). We show here that ligation of CD46 on lymphocytes alters cell polarity, impairing activation and effector function in response to TCR or NK cell receptor signaling.…”
mentioning
confidence: 96%
“…Human CD46 is alternatively spliced into several isoforms, resulting in a varying number of extracellular domains and two different cytoplasmic tails, Cyt1 and Cyt2 (Seya et al, 1999). CD46 seems to be constitutively recycled from the cell surface via clathrin-coated pits and transported to perinuclear multivesicular bodies (Crimeen-Irwin et al, 2003). The importance of CD46 in the homeostasis of the organism is highlighted by its ubiquitous expression on the surface of all nucleated human cells (Liszewski et al, 1991).…”
Section: Cd46 Is a Cellular Receptor For Hhv6 And Measlesmentioning
confidence: 99%